The Role of Tungku Tigo Sajarangan in The Community Development Planning of Minangkabau, Indonesia - Ardieansyah Ardieansyah; Ira Meiyenti; Elvira Mulya Nalien; Ilham Sentosa (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
Tungku Tigo Sajarangan holds a vital role in the deliberation process of the development in the Minangkabau community, regardless of the lack of synergy. This study aims to analyze and describe the position of this customary institution in the development planning of Bukik Batabuah Nagari in Candung District, Agam Regency, West Sumatra Province. The qualitative methods used in the data collection were semi-structured interview techniques comprising 20 informants, as well as field observations and documentation. Subsequently, the results showed that there was synergy from the perspective of individual and behavioral dimensions. Although this synergy was not observed from the position dimension, especially the Cadiak Pandai element, it can still be overcome by mutual control. Concerning the dimensions of the relationship with other parties, Tungku Tigo Sajarangan remains active and participates in providing recommendations and opinions. This activity was observed even though no village regulation came from the Bamus Nagari initiative in implementing the village administration. Consequently, it was concluded that Tungku Tigo Sajarangan has played an active role in the planning process for the development of Bukik Batabuah Nagari. Also, the research recommended that the leadership system should act as a civil society to participate consistently and supervise the policies of the Bukik Batabuah Nagari government, with good synergy and coordination between all related elements.